Documentary Photography from the German Democratic Republic as a Substitute Public - Anne Pfautsch (Humanities, 2018)
This paper discusses artistic documentary photography from the German Democratic Republic (GDR) from the mid-1970s until the fall of the Berlin Wall, and suggests that it functioned as a substitute public–Ersatzöffentlichkeit–in society. This concept of a substitute public sphere sometimes termed a counter-public sphere, relates to GDR literature that, in retrospect, has been allocated this role. On the whole, in critical discourse certain texts have been recognised as being distinct from GDR propaganda which sought to deliver alternative readings in their coded texts. I propose that photography, despite having had a different status to literature in the GDR, adopted similar traits and also functioned as part of a substitute public sphere. These photographers aimed to expose the existing gap between the propagandised and actual life under socialism. They embedded a moral and critical position in their photographs to comment on society and to incite debate. However, it was necessary for these debates to occur in the private sphere, so that artists and their audience would avoid state persecution. In this paper, I review Harald Hauswald’s series Everyday Life (1976–1990) to demonstrate how photographs enabled substitute discourses in visual ways. Hauswald is a representative of artistic documentary photography and although he was never published in the official GDR media, he was the first East German photographer to publish in renowned West German and European media outlets, such as GEO magazine and ZEITmagazin, before the reunification. In 1990, he founded the ‘Ostkreuz–Agency of Photographers’ with six other East German documentary photographers.